(untitled) (International Journal of Engineering and Computer Science, 2017)
Recently, varied development work has been carried out on mobile robots due to their high level performance and accuracy. The autonomous navigation of a mobile robot in an unknown environment has always been a very challenging task. In order to achieve safe and collision free navigation, distance to target is very important and is often estimated by using ultrasound. Ultrasonic measurements are mostly based on determination of TOF. A factor of great importance when assessing the accuracy of ultrasonic range finders is the knowledge of speed of sound, necessary to convert temporal into spatial information. A digital signal-processing technique using Discrete Extended Kalman filter for making an ultrasonic transducer capable of automatically compensating for variations in the speed of sound due to temperature and to reduce the distortion effects of cross correlation estimation is proposed and discussed in this paper. SC-FDMA has become most prominent in broadband uplink wireless systems. Since it offers low distortion and free from PAPR problem which often arises in OFDMA (Orthogonal frequency division multiple access) systems. In this paper wavelets are substituted instead of FFT for this Orthogonality achievement. The discrete wavelets of orthogonal and bi-orthogonal type proves to be best when substituted instead of FFT analysis .The proposed approach shows outstanding performance in terms of BER ,PAPR when compared against the conventional system.